Classical versus quantum equivalence between sine-Gordon, Liouville and other solitons - Dutra, Alvaro de Souza [UNESP]; Amaro de Faria, A. C. [UNESP] (Springer Nature, 2004)
In this work we present a mapping between the classical solutions of the sine-Gordon, Liouville, λφ4 and other kinks in 1+1 dimensions. This is done by using an invariant quantity which relates the models. It is easily shown that this procedure is equivalent to that used to get the so called deformed solitons, as proposed recently by Bazeia et al. [Phys. Rev. D. 66 (2002) 101701(R)]. The classical equivalence is explored in order to relate the solutions of the corresponding models and, as a consequence, try to get new information about them. We discuss also the difficulties and consequences which appear when one tries to extend the deformation in order to take into account the quantum version of the models.
Keywords: Equivalence; Solitons